Good English Teacher Characteristics As Perceived By The Seventh Semester Students Of English Education Departement, Universitas Muhammadiyah Surakarta - SULASMI, Sulasmi; , Aryati Prasetyarini S. Pd, M. Pd (2017)
This study aims to investigate the perception of seventh semester students of English education department about good English teacher characteristics. The characteristics are related to technical knowledge, pedagogy skills, interpersonal skills, and personal qualities. This research is qualitative. The data are analyzed by using qualitative method by Milles and Huberman. The finding of the study shows that students' perception of good English teacher characteristics related to technical knowledge is mastering four English skills (listening, speaking, writing and reading), grammar, vocabulary, pronunciation, explaining material clearly, and managing time. Good English teacher characteristics related to pedagogy skills are managing classroom well, motivating students, giving optimal feedback,using interesting and variety media, applying appropriate and variety techniques,stimulating students active and work in team, evaluating students' academic ability. Good English teacher characteristics related to interpersonal skills are enjoyable, friendly, humorous, communicative, welcoming on teaching technique with colleagues, and maintaining harmonious relationship with other teachers and students. Good English teacher characteristics related to personal qualities are patient, honest, discipline, responsible and good figure. It means that the good English teacher characteristics should be owned by every English teacher to help in conducting teaching learning process.